Modelagem matemática e o ensino de função de 1º grau - Gonçalves Filho, Luiz (2011)
The objective of this research is to develop the application of some activities of the Curricular Proposal State Secretary of Education adapting them to the formation of mathematical models. Given the problems presented by the students, it seeks to, in Mathematical Modeling strategy, a way for learners to be able to understand the concept of function in different forms of representation - algebraic, graphical or by tables. To find out if mathematical modeling is an enabler in understanding the function of Grade 1, it was started with the experience gained in the course of extension Program Building Time - Improving Teacher PEB II (2003), which tackles the subject functions as a tool for modeling and whe chose to work with some of the proposed activities of the Curriculum SEE-SP also functions deal with the same modeling strategy. This study had the participation of students from first grade of high school to a state school. It was analyzed how this group of students answered the questions proposed in which the concept of function was presented, initially, from the relationship between quantities directly proportional. From the modeling of a water bill, sought to develop the concept of function in their various representations by which he could emerge naturally. Finally, a question was raised on a graph so that students make the transition to the algebraic representation. Studies of the Mathematical Modeling of Rodney Carlos Bassanezi were searched to theoretical support